2019
DOI: 10.1002/aoc.4943
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, spectroscopic characterization, calf thymus DNA binding investigation, antioxidant and anticancer activities of some antibiotic azomethine Cu(II), Pd(II), Zn(II) and Cr(III) complexes

Abstract: This study was conducted to prepare novel azomethine chelates of Cu(II), Pd(II), Zn(II) and Cr(III) with tridentate dianionic azomethine OVAP ligand 2-[(2-hydroxyphenylimino)methyl]-6-methoxyphenol. The prepared compounds were characterized using elemental analyses and spectral, conductivity, magnetic and thermal measurements. The spectroscopic data suggest that the parent azomethine ligand binds to the investigated metal ions through both deprotonated phenol oxygen and azomethine nitrogen atoms, and adopts di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 61 publications
1
57
0
Order By: Relevance
“…Moreover, polydentate imine chelators have been found to have plenty of advantages inside their capacity of coordination and biological activity and in the extracting of metals in analytical chemistry . It was reported that minor modifications in the ligand structure having hard/soft atoms such as oxygen, sulfur, and nitrogen have affected the activity of compounds . Cancer is the third leading cause of human mortality worldwide.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Moreover, polydentate imine chelators have been found to have plenty of advantages inside their capacity of coordination and biological activity and in the extracting of metals in analytical chemistry . It was reported that minor modifications in the ligand structure having hard/soft atoms such as oxygen, sulfur, and nitrogen have affected the activity of compounds . Cancer is the third leading cause of human mortality worldwide.…”
Section: Introductionmentioning
confidence: 80%
“…The resulting yellow solid was filtered, washed three times with ethanol, and dried under vacuum in the presence of dehydrated CaCl 2 . SCHEME 1 Synthetic strategy for the preparation of the investigated NBA ligand and its Pd (II) and VO (II) complexes 13 C NMR (δ, ppm), in DMSO-d 6 : 192, 170, 139, 138, 137, 136, 133, 132, 131, 130, 121, 120, 115, and 114.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these results are in accordance with the conductance data. From the FT‐IR spectrum of each complex, the bands that appeared at 505–555 and 449–495 cm –1 in all complexes have been assigned to ʋ(M‐S) and ʋ(M‐N), respectively . These two frequencies support the formation of M–N and M–S bonds.…”
Section: Resultsmentioning
confidence: 99%